2015
DOI: 10.1080/08927014.2015.1080251
|View full text |Cite
|
Sign up to set email alerts
|

Detachment, displacement and reattachment activity in a freshwater byssate mussel (Limnoperna fortunei): the effects of light, temperature and substratum orientation

Abstract: The ability of the freshwater bivalve Limnoperna fortunei to voluntarily detach from the substratum, crawl and reattach as a function of illumination, temperature, substratum orientation, and mussel size was investigated. Thirty-two per cent of the 879 experimental animals detached and reattached elsewhere at least once during five- to eight-day experiments. The proportions of mobile mussels were significantly higher in permanent darkness than under permanent illumination. Displacement distances were also high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…fluminea to estimate filtration activity in the field and reported a circadian rhythm with valves being closed in the morning but open in the afternoon. In addition, Duchini et al (2015) found that Limnoperna fortunei (Dunker, 1857) is more mobile in darkness than in light. Kobak & Nowacki (2007) found that D. polymorpha shows light avoidance behavior.…”
Section: Discussionmentioning
confidence: 99%
“…fluminea to estimate filtration activity in the field and reported a circadian rhythm with valves being closed in the morning but open in the afternoon. In addition, Duchini et al (2015) found that Limnoperna fortunei (Dunker, 1857) is more mobile in darkness than in light. Kobak & Nowacki (2007) found that D. polymorpha shows light avoidance behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Mussels undergo migration under unfavorable conditions, which can be reflected in the secretion and shedding of byssus (Cotéand Jelnikar, 1999;Carrington et al, 2015;Li et al, 2015). Passive migration can be seen as a form of self-protection for mussels when they encounter unfavorable environments, dislodging themselves from the substrate to find suitable habitats (Hunt and Scheibling, 2001;Duchini et al, 2015;Iwasaki, 2015). Hard-shelled mussels (M. coruscus) are more prone to shedding byssus under high temperatures, low pH, and predator presence (Li et al, 2015;Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we adopted two methods to identify mussels that survived cold water exposures at the end of experiment, and both suffer from some uncertainties. First, counting only non‐displaced individuals (10.5%) as survivors can underestimate the survival rate because some mussels might have survived but moved to other locations (within the cage) via release of byssal threads and use of their foot (Duchini et al., 2015). This point is supported by the fact that more large animals were identified at the end of the field exposure (e.g.…”
Section: Discussionmentioning
confidence: 99%